Effects of peer relationship and peer presence on giving and repaying in preschoolers' triad interactions. Issue 2 (15th February 2021) - Li, Xia; Wu, Xiling; Hou, Mulan; Zeng, Meihong; Jiang, Nengzhi; Zhang, Jianxin
Abstract: This study aimed to assess social preferences in dynamic interpersonal interactions among preschool children and to examine the effects of peer relationship (friend vs. stranger) and peer presence (peer presence vs. peer absence) on giving and repaying. Ninety‐nine children participated in a triad game, which consisted of two mixed‐dictator games. The allocations from a proposer in the first dictator game were evaluated as giving, and the allocations from two respondents in the second dictator game were evaluated as repaying friends and strangers. The results indicated that children did not have any specific social preferences for friends in giving and repaying but had altruistic and fair preferences for giving to strangers, and strangers had egoistic preferences in repaying. Furthermore, children allocated more to strangers than to friends and allocated more in peer presence. Besides, friends positively reciprocated to proposers in peer absence and repaid less in peer presence. However, strangers consistently repaid less regardless of whether peers were present or not. These results provide more evidence for the assumption of weak ties in giving and demonstrate the strength of strong ties in repaying. These findings enhance our understanding of the interplay of childhood interactions in the development of early relationships.